Heat tolerance indices as tools for characterizing resilient wheat (Triticum aestivum) RILs population under thermal stress - REDHU, MANDEEP; SINGH, VIKRAM; NIMBAL, SOMVEER; DALAL, MOHINDER SINGH; LANGAYA, SONU; SHARMA, KRITIKA; CHAWLA, RUKOO; POONIA, MUKESH KUMAR (The Indian Journal of Agricultural Sciences, 2023)
The escalating impact of heat stress on agriculture due to climate change has necessitated the development of heat- tolerant crop varieties. To address this, a study was carried out at research farm of CCS Haryana Agricultural University, Hisar, Haryana during winter (rabi) seasons of 2018–19 and 2019–20 under two different environments (normal and late sown). Evaluation of multiple stress indices and their relationship with grain yield per plot was done using 200 recombinant inbred lines (RILs) of wheat (Triticum aestivum L.). Positive correlation was observed between grain yield and stress tolerance index, mean productivity, geometric mean productivity, harmonic mean and mean relative performance, while negative correlations existed with heat susceptibility index, tolerance, stress susceptibility index and reduction under stress conditions. Stepwise regression analysis revealed the importance of mean productivity, yield index, geometric mean productivity, stress tolerance index, and reduction in predicting grain yield. Principal Component Analysis highlighted the significance of tolerance and reduction in explaining the variance, with PC-1 labeled as the resilience and stress tolerance component and PC-2 as the yield stability and performance component. These findings were able to select 13 most heat tolerant RILs, performing better than national level check genotype WH730 and emphasized the role of stress indices especially HSI and TOL in characterizing genotypic responses to heat stress and guiding the selection of heat-tolerant genotypes for sustainable crop improvement. In the context of heat stress tolerance, understanding and harnessing transgressive segregants could lead to the development of crop varieties that not only tolerate, but thrive in challenging environments, ensuring sustainable food production under changing climatic conditions.